Protection of Digital Media using Digital Watermarking - Sarbavidya, S (International Journal of Computer Sciences and Engineering, 2025)
In the present era of Internet, all sorts of digital media (text, audio, video and multimedia) is freely and easily available to everyone over Internet. Anyone can easily access those digital media without taking any sorts of permissions from the owner of the digital media, distribute the digital media freely to others and claim the ownership of the digital media and sometimes make unnecessary changes to the digital media itself. So, the need of the time is to protect the digital media from unauthorized access, restrict free distribution of digital media to others and also to establish the ownership of the digital media in an easy, consistent and efficient manner. In this paper, several approaches using digital watermarking method are proposed, which embeds ownership information and copy protection mechanism within the digital media, to provide a powerful mechanism for protecting digital media in efficient and convenient manner.